Encontros e esperas de uma professora em percurso - Vaz, Tamiris (2013)
This investigation happens with the paths of a researcher which, on meetings with the world, experiments intensities which move her places as a teacher. For so, actions which do not lead necessarily to learning, but to able cracks on crossed roles are lived, as long as collective agencements which make intensity traces pass. Starting on movements given in a specific time and place artistic intervention Waiting Moments, done inside an event called arte#ocupaSM a research which tries to escape those limits is developed, crossing other times and places, including the learning ones, and turning the act of waiting into a space of happenings. Authors as Deleuze, Guattari, Rolnik and Nietzsche bring indicatives to turn this research into paths of not knowing, of unexpected and multiple directions, lived in constant movements of nausea by the impossibility of fixing into a unique teacher place. By not having a unique place to settle, some unpredictable learning happens together with the dogs, the cracks and the rain. Through these, desires to know the world through timeless intensities resonate, knowing we do not choose data and learning to be researched, but we are chosen by them and we produce something with them. So the research allows discussions about the production of cracks on teacher s acting, counting with the unpredictability and uneasiness of raindrops and with the un-preoccupied commitment of dogs on a meet with daily happenings of an inhabited place.